2021
DOI: 10.1002/dys.1699
|View full text |Cite
|
Sign up to set email alerts
|

Phonological working memory and central executive function differ in children with typical development and dyslexia

Abstract: The primary purpose of this study was to compare the working memory performance of monolingual English‐speaking second‐grade children with dyslexia (N = 82) to second‐grade children with typical development (N = 167). Prior to making group comparisons, it is important to demonstrate invariance between working memory models in both groups or between‐group comparisons would not be valid. Thus, we completed invariance testing using a model of working memory that had been validated for children with typical develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 66 publications
2
8
0
2
Order By: Relevance
“…The colour cueing reduced the amount of information students needed to retain in working memory because the colour‐cued exemplar and graphic organizer provided a constant model back to which students could refer as needed. This finding aligns with suggestions (Alt et al, 2021) that students with dyslexia require more working memory supports than their typical peers.…”
Section: Discussionsupporting
confidence: 92%
“…The colour cueing reduced the amount of information students needed to retain in working memory because the colour‐cued exemplar and graphic organizer provided a constant model back to which students could refer as needed. This finding aligns with suggestions (Alt et al, 2021) that students with dyslexia require more working memory supports than their typical peers.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, poor math skills have been repeatedly linked to deficits in multiple aspects of EF, particularly visuospatial working memory (David, 2012;Geary, 2004;Mammarella et al, 2018). RD, independent of MD, has also been associated with poor EF (Alt et al, 2022;Reiter et al, 2005). Akin to the present study, nearly half of children with RD also demonstrated low EF abilities, independent of ADHD diagnoses (Al Dahhan et al, 2022).…”
Section: Behavioral Differences In Ef and Working Memorysupporting
confidence: 52%
“…En los participantes analizados a partir de las pruebas psicométricas suministradas se identificó que a menor fluidez fonológica menor es la repetición de pseudopalabras; este hallazgo concuerda con la investigación realizada por Ehrhorn et al (2020), donde evaluaron 160 niños, divididos en cuatro grupos (desarrollo típico, DS, trastorno de desarrollo del LG y DS-trastorno de desarrollo del LG), midieron la capacidad de repetición de pseudopalabras, encontrando que los puntajes bajos en las tareas de repetición se asocian a deficiencias en la fluidez fonológica en personas con DS. Estos resultados coinciden con los hallazgos del estudio realizado por Loucas et al (2016), quienes evidenciaron una relación directa entre los déficits en la repetición de pseudopalabras y la fluidez fonológica (Cunningham et al, 2021;Nora et al, 2021;Alt et al, 2021;Schraeyen et al, 2019).…”
Section: Discussionunclassified